IMPROVING WRITING ABILITY BY USING GUIDED COMPOSITION AT THE SECOND YEAR OF SMP AL-ISLAM 1 SURAKARTA (CLASSROOM ACTION RESEARCH) - SETYOWATI, YULIA ARI (2011)
This study is aimed at describing the writing ability improvement using guided composition in SMP Al-Islam 1 Surakarta and describing whether teaching writing by using guided composition can improve the writing ability. This is a descriptive qualitative research. The writer applies Classroom Action Research which requires four steps, namely planning, implementing, observing, and reflecting. The subject of the research is 8E class students of SMP Al-Islam 1 Surakarta which consists of 38 students. The methods of collecting data are test (pre and post test), observation, document, and interview. In analyzing the quantitative data the writer applied descriptive comparative technique while in analyzing qualitative data she applied critical analysis technique. The result of this research shows that teaching writing using guided composition can improve the students’ writing ability, which is proven by the improvement of the students’ mean score. The mean score of pre-test is 62, 1 while the mean score of post-test is 83, 4. In addition, the students also feel interested, enthusiastic, motivated and easy in writing class. They also feel easy to express their idea because the teacher gives some guidelines to build their idea.